Thallium(III) p-tosylate (TTS) mediated oxidative rearrangement of 2-naphthyl and 2-heteroarylchromanones - Kurapati, Chidvilas; Muthukrishnan, M.; Singh, V. Om; Gundla, Rambabu (Indian Journal of Chemistry, 2022)
A practical and effective approach towards the synthesis of 3-hetroaryl-4H-chromen-4-ones by the oxidative rearrangement of the respective 2-hetroaryl chroman-4-ones using thallium(III) p-tosylate is described. The oxidative rearrangement of alpha and beta-naphthyl and thiophene behave like aryl groups. However, pyridyl groups give only the dehydrogenated product.
Keywords: 2-(3-pyridyl)chromones; 2-(4-pyridyl)chromones; 2-and 3-(2-theinyl)chromones; 2-and 3-(3-theinyl)chromones; 2-and 3-(?-naphthyl) chromones; Dehydrogenation; Oxidative rearrangements; thallium(III) acetate; thallium(III) p-tosylate